The Influence of Store Atmosphere and Prices on Purchase Decisions Case Study at Identic Coffee Jakarta Pusat - Brigitte Olivia Cahya; T. S. Reza; Dewi Nurbaiti (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Consumers of products and services and goods always consider many things before actually making a decision to buy. Including coffee beverage products, in addition to the price, the shop atmosphere factor is also a consideration for potential consumers. This study aims at determining the effect of Store Atmosphere and Prices on Purchasing Decisions at Identic Coffee in Central Jakarta. This study used quantitative research methods with associative types and primary data as a source of data obtained from questionnaire results. The population of this study was cafe consumers isolated at Cempaka Putih street 114, Central Jakarta with population of 394 people, and samples of 79 people. The analytical methods used is were validity, reliability, normality tests, multiple linear regression correlation coefficient analysis, determinant coefficient test and hypothesis test using SPSS. The results of this study showed that: Store Atmosphere had a positive effect on Purchasing Decisions with a regression value of 0.653 and a significance level of 0.000. Price had a positive effect on Purchasing Decisions with a regression value of 0.686 and a significance level of 0.000. Store Atmosphere and Price simultaneously had a positive effect on Purchasing Decisions with a calculated F value of 13.607 greater than the F tabel of 3.12 and a significance level of 0.000 less than 0.05 (4) The amount of the effect of Store Atmosphere and Price on Purchasing Decision was 77.60% while the remaining 22.40% was effected by other variables not examined by the author.